Most Recent Data (1999). Statistics Canada. CANSIM: International Trade - Merchandise Imports | Country: Canada | Province: Nunavut | Table: Interprovincial and international trade flows at producer prices | Variable: Accommodation services and meals (x 1,000,000), International exports | Units: $CAD, 1999. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-131. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: International Trade - Merchandise Imports | Country: Canada | Province: Nunavut | Table: Interprovincial and international trade flows at producer prices | Variable: Accommodation services and meals (x 1,000,000), International exports | Units: $CAD, 1999. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-131. Dataset: Reports statistics on goods that have entered Canada for consumption. Included are data on on their value, quantities, mode of transport, province of clearance, and country of origin. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: International Relations and Trade Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Imports, Merchandise, International Trade